Accumulation of water stress-responsive class-Ill type of boiling stable peroxidases (BsPOD) in different cultivars of wheat [Triticum aestivum) - Sharma, Arun Dev; Dhuria, Nadia; Rakhra, Gurmeen; Mamik, Shubhneet (Acta Biologica Szegediensis, 2014)
Drought is one of the most important abiotic stress that affects plant growth and productivity. Class-III Peroxidases (PODs) are known to maintain oxidative stress induced-ROS at sub-lethal levels in plants under abiotic stress conditions, but, studies documenting how drought regulates boiling stable class-III PODs are still a matter of conjecture. In this study, changes in total protein content (TPC), water content (WC), H2O2, malondialdehyde (MDA) and ROS scavenging class-III boiling stable POD were studied in the shoots of seven cultivars of wheat at different stages of drought treatment (3 days: D3, 5 days: D5 and 7 days: D7) followed by recovery from stress (post stress: PS). Simultaneous analysis of H2O2, MDA contents and activities of ROS-scavenging class-III boiling stable POD (BsPOD) enzymes gave an integrative view of physiological state and detoxifying potential under conditions of sensitivity and tolerance. Drought stress increased TPC and decreased WC in all the cultivars of wheat. H2O2 content decreased considerably under various stage of drought stress in a genotype dependent manner. As a result, amount of MDA, a product of lipid peroxidation, was also less in all the cultivars at all stress durations. During initial stress conditions (D3), a marked increase in BsPOD activity was observed in cultivars PBW343, PBW550, PBW175, DBW17 and HD2967. An especially high increase (55-fold) was noticed in PBW175 accompanied by enhanced expression of boiling stable POD isoenzyme(s) suggesting that this cultivar has more efficient mechanisms to scavenge ROS species. In addition, this cultivar has also maintained higher BsPOD activity when the stress duration increased from D3 to D7. The other cultivars having lowest enzyme activities are mentioned as cultivars sensitive to drought stress. Compared to stress, significantly higher soluble protein content accompanied by BsPOD activity was observed after the exposure to recovery conditions in the majority of cultivars. Based on these results, the possible role of BsPOD activity and isoenzyme(s) to perform biological antioxidative reactions to combat drought-induced oxidative stress was discussed.